The Influence of Vowels on Vocal Fold Dynamics in the Tenor's Passaggio - Echternach, Matthias; Burk, Fabian; Koeberlein, Marie; Burdumy, Michael; Döllinger, Michael; Richter, Bernhard (Journal of Voice, 2017)
INTRODUCTION: The influence of vowels on the frequency region where registration events in male voices usually occur (passaggio) has not yet been clarified. Particularly, for tenors who frequently have to sing across the passaggio, it might be assumed that the vowel quality has an influence on the stability of phonation. METHODS: In this investigation, six professionally trained Western classical tenors performed a glide from A3 (220 Hz) to A4 (440 Hz) and were recorded using high-speed videoendoscopy at 20,000 fps via transnasal flexible endoscopy. The participants produced transitions (1) from modal register to falsetto and (2) from modal register to stage voice above the passaggio on the vowels [aː], [iː], and [uː]. Simultaneously, acoustic and electroglottographic (EGG) signals were recorded. The glottal area waveform (GAW) open quotient (OQ), the EGG OQ, and the sample entropy derived from the EGG were calculated and phonovibrograms were established. RESULTS: In comparison to [iː] and [uː], vowel [aː] showed lower values regarding the sample entropy and greater periodicity in the phonovibrograms during the passaggio. For [iː] and [uː], the falsetto showed greater GAW OQ than the stage voice above the passaggio but no great difference for vowel [aː]. There was a good agreement between GAW OQ and EGG OQ for GAW OQ values below .65. However, for values greater than .65, the EGG OQ showed greater disagreement. CONCLUSIONS: The data support the hypothesis that the vowel condition influences the phonatory stability concerning the passaggio, suggesting that vowel [aː] is associated with greater phonation stability.
EVALuna2:33366